39.3k views
2 votes
What is the answer??????

What is the answer??????-example-1
User Tvb
by
5.7k points

2 Answers

3 votes

The answer is D. D is the answer

User Lee Grissom
by
5.0k points
4 votes

Answer:

D. G(x) = (x + 3)²

Explanation:

f(x) - n - shift the graph n units down

f(x) + n - shift the graph n units up

f(x - n) - shift the graph n units to the right

f(x + n) - shift the graph n units to the left

==========================================

From the graph:

G(x) - the graph F(x) has been shifted 3 units to the left (look at the vertex).

Therefore your answer is G(x) = F(x + 3) = (x + 3)²

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.